Legal Certainty of Electronic Certificates In National Land Law Reform in The Digital Transformation Era - Rahmat, Rahmat; Iriantoro, Agung; Surono, Agus (Dinasti Research, 2025)
This article explores the legal legitimacy and challenges in the implementation of electronic land certificates (e-certificates) within Indonesia’s national land administration system, while examining the concept of immutability the inability to alter data in the context of land law. It discusses the legal foundations, implementation processes, evidentiary strength, as well as technical and regulatory challenges, highlighting the potential of e-certificates as instruments that enhance legal certainty and security in the digital era of land administration. The digital transformation of Indonesia’s national land system introduces a significant innovation in the form of electronic land ownership certificates (e-certificates), aimed at improving efficiency, accountability, and legal certainty in land administration. This article critically examines the legal legitimacy, normative basis, and practical implications of implementing e-certificates within the framework of national land law, with a primary focus on the application of the principle of immutability, whereby data cannot be changed or manipulated without a legitimate audit trail. Using a normative juridical approach and empirical analysis based on primary data, this article identifies several implementation challenges including vulnerabilities in information systems, infrastructure gaps, suboptimal legal evidentiary mechanisms in court, and social resistance to the digitization of land ownership documents. The success of e-certificate implementation is highly dependent on data interoperability, resilient system design, and regulatory clarity regarding digital legal evidence. Digital transformation has become a national strategic agenda for bureaucratic modernization and improving public service quality, as outlined in Peraturan Presiden Nomor 95 Tahun 2018 on the Electronic-Based Government System (SPBE). One of the sectors undergoing accelerated digitalization is land administration, through the implementation of electronic certificates by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN), Peraturan Menteri ATR/BPN Nomor 3 Tahun 2023 concerning Electronic Documents. This initiative aims to create efficient, transparent, and integrated land registration services. However, the use of e-certificates as legal evidence of land rights presents both normative and practical challenges within the national legal system particularly regarding evidentiary strength, document legality, and data integrity and authentication safeguards. The effectiveness of e-certificate implementation depends on a legal system that is adaptive to technology, supported by a digital architecture that incorporates the principle of immutability through cryptographic technology, audit trails, and potential blockchain utilization. Thus, the certificate becomes not only an administrative tool but also a new foundation for the protection of agrarian rights in the digital era. These findings are relevant for policymakers, academics, and land practitioners in designing a modern, inclusive, and legally protective national land system.